Réponses

2014-10-21T13:14:34+02:00

5x + 1 = - 2

5x + 1 - 1 = - 2 - 1

5x = - 3

5x/5 = - 3/5

x = - 0,6


2x² + 1 = 3

2x² + 1 - 1 = 3 - 1

2x² = 2

2x² = 2

x = √2


- x - 1 = 10

- x - 1 + 1 = 10 + 1

- x = - 11


- 5x² + 4 = - 4

- 5x² + 4 - 4 = - 4 - 4

-5x² = - 8



2014-10-21T13:26:27+02:00
Bonjour

5 x +1 = - 2
5 x = - 2 -1
5 x = -3
x = -3/5

2x² +1 = 3

2 x ² = 3 -1
2 x² = 2
x² = 1
x = √1

- x -1 = 10
- x = 10 + 1
- x = 11
x = -11

- 5x ² +4 = - 4
- 5 x² = - 4 -4
 - 5 x² = -8
x² = 8/5
x = √8/5

- 2x ² - 1 = -1
- 2x² = - 1 +1
 - x ² = 0
x = 0

4 x² +4 = 4
4 x² = 4 -4
 4x² = 0
x = 0